Marketing Strategies Of Processed Cassava Businesses In Improving Community Welfare Islamic Economic Review (Case Study Of Cempedak Lobang Village) - Andri Widiaini; Muhammad Ikhsan Harahap; Aqwa Naser Daulay (UNIVED Press, 2024)
This research aims to explore the Cassava Business Development Model in Improving Community Welfare with an Islamic Economic Approach in Cempedak Lobang Village. Descriptive qualitative methods and interviews were used to highlight the application of Islamic economic concepts which emphasize partnerships and sharing risks and benefits, strengthening inclusiveness and sustainable local economic development. The SWOT analysis highlights the strengths, weaknesses, opportunities, and threats related to developing a cassava business in Cempedak Lobang Village, including abundant natural resources, community involvement, lack of infrastructure, and market opportunities for organic cassava products. In addition, S-O (Strengths-Opportunities) Strategy is an approach that utilizes the internal strengths of an entity to pursue existing external opportunities. In the context of cassava business development in Cempedak Lobang Village, the S-O strategy can be applied to maximize the positive potential of the village and utilize it to take advantage of emerging opportunities. Threats may arise from market competition and climate change. By considering these factors, the cassava business development model in Cempedak Lobang Village can be improved to achieve better prosperity for the local community.